PEMANFAATAN SUSU KEDELAI DAN EKSTRAK UMBI BIT DALAM PEMBUATAN ES KRIM - Liana Liana; Dewi Fortuna Ayu; Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was obtained the right formulation soybean milk and beetextract in the manufactureof ice cream. The research used a Complete Randomized (CRD) with five treatments and three replications which were followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatments in this research were KB1 (soybean milk 100), KB2 (Soybean milk 90 :beetextract10), KB3 (Soybean milk 80 :beetextract20), KB4 (Soybean milk 70 : beet extract30), KB5 (Soybean milk 60 : beetextract40). The analyze observed were overrun, melting time, total solid, fat content and sensory test.The result of analysis showed that the formulation of soybean milk and beetextractsignificantly effect on overrun, melting time, total solid, fat content and organoleptic test.The best formulation ice cream was soybean milk 90 : beet extract 10 with overrun 70.33%, melting time 18.43 minutes, total solid 37.32%, and fat content3.21%. Organoleptic scores of the best treatment were 3.20 (pink), 3.43 (between soybean milk flavour and beet flavour), 3.27 (little soybean taste), 2.70 (little rough texture), and 4.16 (overall) assesment of ice cream. Keywords: Ice cream, soybean milk and beet extract.